SAT0456 Long-Term Effects of Treatment on The Progression of Structural Changes in Knee Osteoarthritis: 6-Year Follow-Up. (15th July 2016) - Marte-Pelletier, J.; Raynauld, J.P.; Abram, F.; Delorme, P.; Pelletier, J.P.
Abstract : Background: The Osteoarthritis Initiative (OAI) is the largest knee osteoarthritis observational cohort. It provides the possibility to study the evolution of OA structural changes over time and the associated risk factors. It also allows the potential disease-modifying OA drug effects to be explored in patients over time. Objectives: This study aimed to examine, for the first time, the long-term (6-year) protective effect of combined glucosamine (Glu) and chondroitin sulfate (CS) treatment on OA knee cartilage volume using the OAI cohort. Methods: Participants from the OAI Progression and Incidence sub-cohorts who had MRI data on the target knee at baseline and at 6 years and with a JSW greater than 1 mm, and information on the Glu/CS consumption were included (n=1593). The participants were stratified into two main groups based on whether or not they had medial meniscal extrusion at baseline, and the former group (n=429) were further stratified into subgroups based on their exposure time: not exposed, 1 year, 2 to 3 years, and 4 to 6 years. MRI assessments were done using fully automated quantitative technologies 1, 2 . Statistical analysis included the Jonckheere-Terpstra trend test as well as multivariate analysis test. Results: Findings indicate that in participants with knee OA, treatment with the combined Glu/CS significantly reduced the loss of cartilage in the global knee associated with the lateral compartment. Moreover, the extent of the treatment's positive effect was also found to be related to the exposure time to treatment, the protective effect at 6 years being significant in participants who were exposed to 2 or more years of treatment. Conclusions: The findings of this study are in line with previous data showing chondroprotective effects of glucosamine and chondroitin sulfate treatment with preferential effects, and provide future support for the long-term structure-modifying effects of such treatment in knee osteoarthritis subjects. References: Dodin P, Pelletier JP, Martel-Pelletier J, Abram F. IEEE Trans Biomed Eng. 2010;57:2699–711. Dodin P, Abram F, Pelletier JP, Martel-Pelletier J. J Biomed Graph Comput. 2013;3:51–65. Disclosure of Interest: J. Marte-Pelletier Shareholder of: Arthrolab Inc., Grant/research support from: Bioiberica, Consultant for: Bioiberica, J. P. Raynauld: None declared, F. Abram: None declared, P. Delorme: None declared, J. P. Pelletier Shareholder of: Arthrolab Inc., Grant/research support from: Bioiberica, Consultant for: Bioiberica, Speakers bureau: Bioiberica